Intensive Systolic Blood Pressure Lowering and Kidney Disease Progression in IgA Nephropathy: A Cohort Study - Yu, Guizhen; Cheng, Jun; Jiang, Yan; Li, Heng; Li, Xiayu; Chen, Jianghua (Frontiers in Medicine, 2022)
Background: Hypertension has been shown to be an important risk factor in IgAN. The 2021 KDIGO Guideline proposes a target systolic blood pressure (SBP) of less than 120 mmHg in patients with CKD not receiving dialysis. However, whether lowering SBP from <140mm Hg to < 120mm Hg is renoprotective is unknown. This study aims to evaluate the association of SBP and progression of IgAN, then explore whether lowering SBP from <140 mm Hg to < 120mm Hg is renoprotective. Methods: Overall, 2240 IgAN patients were enrolled in this study, Cox proportional hazards models and restricted cubic splines were used to estimate the associations between SBP and kidney failure event which defined as 50% estimated glomerular filtration rate (eGFR) decline or kidney failure. Results: After a median follow-up of 30.05 months, 217 (9.69%) patients reached composite kidney failure events. The association of SBP and kidney failure events showed a liner relationship. The risk of kidney failure events was greater with higher SBP. Compared with SBP <120mm Hg, the hazard ratio was 1.85 (1.16-2.97, p=0.010) for SBP < 140mm Hg after adjustment for traditional risk factors. The renoprotective benefits of therapy targeting SBP<120mm Hg from SBP < 140mm Hg was detectable within the subgroup with proteinuria > 1.0 g/d, CKD 1-3a stage, but not those with proteinuria ≤1.0 g/d and CKD 3b-4 stage. Conclusions: In IgAN patients, SBP was independently associated with composite kidney failure events. Lowering SBP from <140mm Hg to < 120mm Hg was renoprotective.